2012
DOI: 10.1121/1.3699265
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spectral smearing on the identification of speech in noise filtered into low- and mid-frequency regions

Abstract: Léger et al. [J. Acoust. Soc. Am. 131, 1502-1514 (2012)] reported deficits in the identification of consonants in noise by hearing-impaired listeners using stimuli filtered into low- or mid-frequency regions in which audiometric thresholds were normal or near-normal. The deficits could not be fully explained in terms of reduced audibility or temporal-envelope processing. However, previous studies indicate that the listeners may have had reduced frequency selectivity, with auditory filters broadened by a factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 49 publications
2
7
2
Order By: Relevance
“…This may indicate that audibility influenced speech intelligibility, even though the speech was amplified for listeners with PTAs above 20 dB HL in the tested region. This finding is at odd with the results of Léger et al (2012a), for which the audiometric thresholds in the tested regions were not correlated with the speech scores. The values of the extended speech intelligibility index (ESII; Rhebergen and Versfeld, 2005;Rhebergen et al, 2006) were calculated for each listener tested here.…”
Section: Origin Of the Suprathreshold Auditory Deficitscontrasting
confidence: 74%
See 3 more Smart Citations
“…This may indicate that audibility influenced speech intelligibility, even though the speech was amplified for listeners with PTAs above 20 dB HL in the tested region. This finding is at odd with the results of Léger et al (2012a), for which the audiometric thresholds in the tested regions were not correlated with the speech scores. The values of the extended speech intelligibility index (ESII; Rhebergen and Versfeld, 2005;Rhebergen et al, 2006) were calculated for each listener tested here.…”
Section: Origin Of the Suprathreshold Auditory Deficitscontrasting
confidence: 74%
“…Simulated mild broadening of the auditory filters had very little effect on speech intelligibility. Léger et al (2012a) concluded that, consistent with previous work of Strelcyk and Dau (2009), slightly reduced frequency selectivity could not entirely explain the speech perception deficits for HI listeners found by Léger et al (2012b).…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…Previous research suggests strong links between a number of basic auditory abilities in older and hearingimpaired listeners and the perception of speech interrupted by silence or modulated noise. These include forward masking, TFS processing, low-to-mid frequency audibility, and auditory filter bandwidth Nelson, 2006, 2010;Leger et al, 2012;Sheft et al, 2012a). The age-related deficits in temporal processing, however, appeared most detrimental at high interruption rates, while having less of an effect at slower rates F€ ullgrabe et al, 2006).…”
Section: Introductionmentioning
confidence: 99%